Using Graduated Guidance to Teach Spoon Use to Children with Severe Multiple Disabilities Including Visual Impairment. (December 2018) - Ivy, Sarah E.; Hatton, Deborah D.; Wehby, Joseph H.
Children's skill level in using a spoon facilitates increased independence during mealtimes and greater control over the pace and quantity of food intake, which has important implications for health and self-determination. Children with severe multiple disabilities, including cognitive and visual impairment (VI), require intensive instruction to achieve independence using a spoon. We used graduated guidance and verbal prompting to teach spoon use to three children with severe multiple disabilities, including cognitive and VI, in a pullout setting during afternoon snack at school. Efficacy of the intervention was tested using a multiple probe design across participants. Results show that the intervention was associated with an increase in participants' independent, accurate spoon use; although, in the time allotted, participants did not reach full independence with all steps of spoon use. Implications for practice and future research are discussed.